1996
DOI: 10.1001/archneur.1996.00550060035012
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Symptoms Do Not Correlate With Cognitive Decline, Motor Symptoms, or CAG Repeat Length in Huntington's Disease

Abstract: The lack of correlation between disease severity and psychiatric disturbances indicates that psychiatric disorders progress nonlinearly, possibly because of differential degeneration of the striatal-cortical circuits; the possibility that psychiatric disorders are prevalent in certain families with a member who has Huntington's disease is being further investigated. The lack of correlation between CAG length and cognitive and psychiatric variables needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
47
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(61 citation statements)
references
References 44 publications
11
47
3
Order By: Relevance
“…Still others experience marked motor, mood, and cognitive symptoms simultaneously (Brandt and Butters 1986;Folstein 1989;Myers et al 1991;Claes et al 1995;Zappacosta et al 1996; Thompson et al 2002). Interestingly, observations in monozygotic twins who inherited identical HTT genes with the same repeat length exhibit marked differences in their symptom profile (Georgiou et al 1999;Friedman et al 2005;Gomez-Esteban et al 2007).…”
Section: Symptomatologymentioning
confidence: 99%
“…Still others experience marked motor, mood, and cognitive symptoms simultaneously (Brandt and Butters 1986;Folstein 1989;Myers et al 1991;Claes et al 1995;Zappacosta et al 1996; Thompson et al 2002). Interestingly, observations in monozygotic twins who inherited identical HTT genes with the same repeat length exhibit marked differences in their symptom profile (Georgiou et al 1999;Friedman et al 2005;Gomez-Esteban et al 2007).…”
Section: Symptomatologymentioning
confidence: 99%
“…49,51,95,125,126,[154][155][156]158,160,[162][163][164] Finally, HD and PD patients are impaired on "frontal" neuropsychological tests, such as the stylus maze, verbal fluency, Tower of Toronto, and the Wisconsin Card Sorting Test. 49,70,81,95,[155][156][157]161,[165][166][167][168][169][170][171] There are, however, some differences between the cognitive deficits in HD and PD, although these are often overlooked. HD but not PD patients are reported to have concentration difficulties.…”
Section: Cognitive Symptomsmentioning
confidence: 99%
“…The most prevalent behavioral disturbances associated with HD include: (1) personality and behavioral changes, which include on the one hand impulsive and erratic behavior, increased irritability, aggressiveness and labile mood, and on the other hand, reduced spontaneity and initiative; 49,50,125,126,193 and (2) definable psychiatric disorders, namely, depressive and manic-depressive mood disorder, schizophreniform psychosis, and less commonly, obsessive compulsive disorder. 50,51,125,126,171,[193][194][195][196][197] Since damage to the frontal cortex or basal ganglia can lead to symptoms similar to those outlined above, 96,[198][199][200] the emotional disturbances in HD were suggested to reflect disturbed frontostriatal functioning. 96,201 As noted above, Litvan et al 101 suggested that the symptoms of agitation, irritation, and euphoria in HD are secondary to underactivity of the indirect pathways which arise from the ventromedial caudate and ventral striatum, respectively.…”
Section: Emotional Symptomsmentioning
confidence: 99%
“…Also, MTR and COG were significantly related: Those with worse motor function (i.e., higher motor scores) also had worse cognitive function (i.e., lower cognitive scores). (Zappacosta et al, 1996). The only apparent exception to this general rule appears to be apathy, which does relate to cognitive decline in HD (Baudic et al, 2006).…”
Section: Resultsmentioning
confidence: 99%